Still safe? Still in their hands? An evaluation of NHS privatisation in England since 2010 - Goodair, B (2024)

(untitled)
England’s NHS has experienced increased privatisation via a shift towards the contracting-out of publicly funded healthcare to private providers. Originally founded through a widespread nationalisation of hospitals, the NHS (National Health Service) is considered a symbol of national pride as the crown jewel in the welfare state and one of the core achievements of socialism in post-war Britain. This has made the privatisation of the service a site of fervent political and public discourse. Yet, missing from this debate has been the input of rigorous research into the extent and impacts of privatisation. Given the importance of healthcare provision to population health, it is crucial to understand why the NHS has been privatised and whether privatisation has improved or worsened healthcare quality. This thesis makes three major contributions to these debates by answering: a) what are the causes of NHS privatisation, b) what is the extent of privatisation, and c) what are the impacts of privatisation on healthcare quality?